BERTANAM PUCUK IDAT UNTUK ANAK-ANAK DI RUSUNAWA PANGKAL BALAM - Nurulfiyanti, Tania; Sukina, Marwia; Anderika, Putri; Intrisca, Anggun; Herlinda, Leni; Syafi’i, M. Arief; Annisa, Siti Nur; Claudia, Sindi; Winiyarti, Tiya; Septiani, Widya Asri (Unmuh Babel Press, 2024)
Greening is one of the important activities carried out in dealing with the environmental crisis in the surrounding area. Ketapang Village, Pangkal Balam Subdistrict is one of the effective objects to do greening, because the local children are very enthusiastic in making awareness of the importance of greening in their environment and besides that the environment there is very conducive to greening. The target of this activity is the preservation of greening in community areas where there is still vacant land for greening. The main objective of this research is to give children an understanding of the benefits of idat shoots which is one of the environmental conservation actions of reforestation and other benefits. The research method used participatory observation method with field survey data collection techniques through lectures and direct field practice. The results of this research are the definition of greening, the benefits of greening and direct simulation of greening.